2013
DOI: 10.3109/17518423.2013.857735
|View full text |Cite
|
Sign up to set email alerts
|

Australian parents’ experiences of speech generating device (SGD) service delivery

Abstract: Having an SGD at home generates ongoing support needs, which had not been well met for some parents in our study. Results suggest that timely, well coordinated and family-centred support may enhance service experience for families with a new device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 33 publications
2
36
1
Order By: Relevance
“…Moreover, training in using the technology has been shown to positively affect the outcomes of the service delivery process for AT users [6,11] and to support more individually appropriate choices of the technology [12]. Such findings confirm that taking a client-centred approach in the service delivery process is important to satisfy AT users [6,11,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Moreover, training in using the technology has been shown to positively affect the outcomes of the service delivery process for AT users [6,11] and to support more individually appropriate choices of the technology [12]. Such findings confirm that taking a client-centred approach in the service delivery process is important to satisfy AT users [6,11,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 78%
“…Instead, different actors-the municipality, the Assistive Technology Centre, and suppliers-all with different interests take responsibility for different steps of the service delivery process. In that case, research has shown that a prerequisite for a client-centred approach is teamwork, described as collaboration by team members within and across clients, caregivers, therapists, and organisations [14]. When roles and responsibilities are unclear in that approach, the process becomes needlessly complex, complicates the accessibility of information, and lessens control over the process, especially for users [6,12,17,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This expectation is supported by Anderson, Balandin, and Stancliffe (2014), who reported that despite their frustrations, not all parents were willing to voice their concerns about the AAC service they received. In addition, parents reported the importance of well-established formal and informal support systems when AAC is introduced (Lindsay, 2010;Lund & Light, 2006).…”
Section: Stakeholder Experiences With Aacmentioning
confidence: 97%
“…Parents reported linking themselves with various online networks for resources and support, however SLPs questioned the appropriateness and implementation of the acquired resources (Anderson et al, 2015). Furthermore, Anderson et al (2014) described the impact of policy barriers to accessing AAC services, including age or eligibility restrictions, and single-service exclusion policies. Inappropriate access to services was extremely detrimental, with three of the six parents interviewed reporting the abandonment of high-tech AAC devices due to the absence of frequent professional guidance and encouragement.…”
Section: Stakeholder Experiences With Aacmentioning
confidence: 99%